2012
DOI: 10.1159/000342890
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Recovery of Ventilator-Associated Pneumothorax

Abstract: Background: The usual management of ventilator-associated pneumothorax (VPX) is tube thoracostomy. However, this recommendation is based on tradition rather than on solid evidence. Although it has been applied successfully to other types of pneumothoraces, observation has not been used in the management of VPX. Objectives: In this study, we investigated whether observation is a valid treatment strategy for VPX. Methods: We retrospectively analyzed data of 471 patients with VPX (2003-2010) and found that 27 did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…To maintain satisfactory oxygenation, a high PEEP value during ventilation was generally used, which possibly led to tension pneumothorax, especially when lung consolidation and pulmonary fibrosis developed. Once plural effusion or pneumothorax happened, the effective ventilation area decreased dramatically so that the hypoxemia was aggravated with a fatality [ 24 , 25 ]. Therefore, bedside lung ultrasonography could help us to discover pulmonary morphological changes in a timely manner and guide the puncture accurately, leading to a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain satisfactory oxygenation, a high PEEP value during ventilation was generally used, which possibly led to tension pneumothorax, especially when lung consolidation and pulmonary fibrosis developed. Once plural effusion or pneumothorax happened, the effective ventilation area decreased dramatically so that the hypoxemia was aggravated with a fatality [ 24 , 25 ]. Therefore, bedside lung ultrasonography could help us to discover pulmonary morphological changes in a timely manner and guide the puncture accurately, leading to a favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on a retrospective study in 74 patients that was published almost 4 decades ago [4], which reported signs of a tension component in 95% and a high mortality rate of 30% if drainage was delayed. However, in the observational study by Wu et al [5 ]in this issue of Respiration , this standard of care is questioned. The authors describe the outcome of a ventilator-associated pneumothorax without intervention in a group of 27 patients.…”
mentioning
confidence: 99%
“…Particularly for such patients, a conservative approach may prevent prolonged hospitalization during active treatment of the pneumothorax. Confirmation in the form of an observational phase-II-type study would be appropriate to determine whether the findings of Wu et al [5] should lead to a change in current practice.…”
mentioning
confidence: 99%